Is there a retirement consumption puzzle in Italy? - Raffaele Miniaci; Chiara Monfardini; Guglielmo Weber (Institute for Fiscal Studies (IFS), 2003)
In this paper we investigate the way consumption changes around retirement in Italy. Using micro data covering the 1985-96 period, we find that consumption age patterns are similar to those found in the US and other developed countries, despite the much more wide-spread cohabitation of different generations. We also document the existence of a one-off drop in consumption at retirement of the household head, as in the UK and the US, and find that consumption of work-related goods falls around retirement age and home production of food and other goods increases. Given that we can provide evidence that Italian households who retired over the sample period knew reasonably well what their pension income would be, the only reason why forward looking consumers should reduce spending around retirement is because of their increased consumption of leisure. We do find evidence that the abrupt falls in total non-durable consumption at retirement disappear when leisure is taken into account, in agreement with the predictions of the life-cycle theory. This finding is robust to the way consumption is attributed to different household members, and to exclusion of non-nuclear households from the analysis.
Keywords: 330; Verbraucherausgaben; Altersgrenze; Italien